Ceria Zirconia Mixed Oxides Prepared by Hydrothermal Templating Method for the Oxidation of Ethyl Benzene - Cimi A Daniel; S. Sugunan (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
CeO2–ZrO2 oxides were prepared by the surfactant-templated method using cetyl trimethyl ammonium bromide (CTAB) as template. These were characterized by XRD, FT-IR, TEM, SEM, BET and TPD-CO2. The XRD data showed that as prepared CeO2-ZrO2 powder particles have single phase cubic fluorite structure. HRTEM shows mesoscopic ordering. Average particle size is 12-13 nm as calculated from particle histogram. The nitrogen adsorption/desorption isotherm were classified to be type IV isotherm, typical of mesoporous material. The presence of uni-modal mesopores are confirmed by the pore size distribution which shows pore distribution at around 60 A°. The catalytic activities of the prepared material were tested in liquid phase oxidation of ethylbenzene with tert-butyl hydroperoxide (TBHP) as an oxidant. Ceria zirconia catalyst modified with chromium was active for ethylbenzene conversion (65.3%) with 77% selectivity towards acetophenone.  © 2013 BCREC UNDIP. All rights reserved Received: 4th June 2013; Revised: 20th July 2013; Accepted: 18th August 2013 [How to Cite: Daniel, C.A., Sugunan, S. (2013). Ceria Zirconia Mixed Oxides Prepared by Hydrothermal Templating Method for the Oxidation of Ethyl Benzene. Bulletin of Chemical Reaction Engineering & Catalysis, 8 (2): 97-104. (doi:10.9767/bcrec.8.2.5053.97-104)] [Permalink/DOI: http://dx.doi.org/10.9767/bcrec.8.2.5053.97-104]